A Novel Maturation Function for Clearance of the Cytochrome P450 3A Substrate Midazolam from Preterm Neonates to Adults - Ince, Ibrahim; de Wildt, Saskia N.; Wang, Chengueng; Peeters, Mariska Y. M.; Burggraaf, Jacobus; Jacqz-Aigrain, Evelyne; van den Anker, John N.; Tibboel, Dick; Danhof, Meindert; Knibbe, Catherijne A. J. (Clinical pharmacokinetics, 2013)
Background and objective Major changes in cytochrome P450 (CYP) 3A activity may be expected in the first few months of life with, later, relatively limited changes. In this analysis we studied the maturation of in vivo CYP3A-mediated clearance of midazolam, as model drug, from preterm neonates of 26 weeks gestational age (GA) to adults. Methods Pharmacokinetic data after intravenous administration of midazolam were obtained from six previously reported studies. Subjects were premature neonates ( n = 24; GA 26–33.5 weeks, postnatal age (PNA) 3–11 days, and n = 24; GA 26–37 weeks, PNA 0–1 days), 23 children after elective major craniofacial surgery (age 3–23 months), 18 pediatric intensive-care patients (age 2 days–17 years), 18 pediatric oncology patients (age 3–16 years), and 20 healthy male adults (age 20–31 years). Population pharmacokinetic modeling with systematic covariate analysis was performed by use of NONMEM v6.2. Results Across the entire lifespan from premature neonates to adults, bodyweight was a significant covariate for midazolam clearance. The effect of bodyweight was best described by use of an allometric equation with an exponent changing with bodyweight in an exponential manner from 0.84 for preterm neonates (0.77 kg) to 0.44 for adults (89 kg), showing that the most rapid maturation occurs during the youngest age range. Conclusions An in-vivo maturation function for midazolam clearance from premature neonates to adults has been developed. This function can be used to derive evidence-based doses for children, and to simulate exposure to midazolam and possibly other CYP3A substrates across the pediatric age range in population pharmacokinetic models or physiologically based pharmacokinetic models.